Rice quality: How is it defined by consumers, industry, food scientists, and geneticists?. (October 2019) - Custodio, Marie Claire; Cuevas, Rosa Paula; Ynion, Jhoanne; Laborte, Alice G.; Velasco, Maria Lourdes; Demont, Matty
Abstract: Background: Quality is a powerful engine in rice value chain upgrading. However, there is no consensus on how "rice quality" should be defined and measured in the rice sector. Scope and approach: We adopt a Lancasterian definition of rice quality as a bundle of intrinsic and extrinsic attributes. We then review how rice quality is (i) perceived and defined by consumers and industry stakeholders in rice value chains in Southeast and South Asia; (ii) measured and defined by food technologists; and (iii) predicted through genetics. Key findings and conclusions: Consumers are heterogeneous with respect to their perceived differentiation of rice quality among regions, countries, cities, and urbanization levels. Premium quality is defined by nutritional benefits, softness and aroma in Southeast Asia, and by the physical appearance of the grains (uniformity, whiteness, slenderness), satiety, and aroma in South Asia. These trends are found to be consistent with industry perceptions and have important implications for regional and national breeding programs in terms of tailoring germplasm to regions and rice varieties to specific local market segments. Because rice is traded internationally, there is a need to standardize definitions of rice quality. However, food technologists have not reached unanimity on quality classes and measurement; routine indicators need to be complemented by descriptive profiles elicited through sensory evaluation panels. Finally, because rice quality is controlled by multiple interacting genes expressed through environmental conditions, predicting grain quality requires associating genetic information with grain quality phenotypes in different environments. Highlights: Consumers perceive rice quality differently among regions, countries, and urbanization levels. In Southeast Asia, nutritional benefits, softness and aroma define premium quality. In South Asia, physical appearance of grains and satiety define premium quality. Current rice quality protocols and classification ranges need to be standardized. Rice quality is coded by genes whose expressions are affected by the environment.